Inter-race soccer and the 1960 riots in Durban, South Africa (Historia, 2021)
The 1950s were witness to experiments in "inter-race" soccer because racially-based African, Indian, and Coloured teams played against each other at provincial and national levels. Sports officials felt that this was a positive development as teams were breaking racial barriers. However, as the decade wore on and the Defiance Campaign of 1952 and the Treason Trial (1956-1961) heightened political consciousness, sports officials and many activists came to believe that racialised teams were anomalous and were in fact exacerbating race consciousness. The fears of critics of inter-race soccer matches materialised when riots broke out at a soccer match between the South African Indian XI and the South African Africans XI at Curries Fountain, Durban, on 31 July 1960. These riots took on racial overtones. This article discusses the inauguration of inter-race tournaments, the riots themselves, and the aftermath of the riots. A key argument is that the riots played an important role in bringing about non-racial football in South Africa in the 1960s. Gedurende die 1950s het eksperimente in "veel-rassige" sokker plaasgevind. Rasgebaseerde swart, Indier en gekleurde spanne het op provinsiale en nasionale vlak teen mekaar gespeel. Sportamptenare het gevoel dat dit 'n positiewe ontwikkeling was, en dat rasseskeidings deurbreek is. In die loop van die dekade het veldtogte van verset en die hofsaak van hoogveraad (Treason Trial, 1956-1961) egter politieke bewussyn aangewakker. Talle aktiviste het standpunt ingeneem op die saamstel van spanne op 'n rassebasis en was oortuig dat rassebewussyn so aangewakker word. Die vrese van die kritici van veelrasigge sokker is bewaarheid toe onluste uitgebreek het gedurende 'n sokkerwedstryd tussen twee spanne, die Suid-Afrikaanse Indiese XI en die Suid-Afrikaanse swart XI by Curries Fountain, Durban, op 31 Julie 1960. Hierdie artikel bespreek die daarstelling van veelrassige toernooie, die onluste en die nadraai van die onluste. 'n Belangrike argument is dat die onluste 'n belangrike rol in die totstandkoming van nie-rassige sokker in Suid-Afrika gedurende die 1960s.